Adhesive, adhesive tape, and method for manufacturing adhesive
A solvent-free adhesive composition using a urethane prepolymer, polythiol, and photoreactive monomer with a tackifier addresses the challenges of maintaining adhesive strength and temperature resistance, ensuring effective performance in high-temperature environments.
Patent Information
- Application Number
- JP2023017897
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-02-08
- Publication Date
- 2025-01-08
- Estimated Expiration
- 2039-06-26
AI Technical Summary
Existing adhesives face challenges in maintaining sufficient adhesive strength, peel creep properties, high-temperature peel strength, and high-temperature holding power when used in high-temperature environments, and they often require solvents, which pose environmental and health risks.
A composition comprising a urethane prepolymer, a polythiol with a thiol group, a monomer with a photoreactive functional group, and a tackifier, blended in specific ratios and molecular weights, is crosslinked through an ene-thiol reaction to form an adhesive that can withstand high temperatures without solvents.
The adhesive achieves sufficient adhesive strength, peel creep properties, high-temperature peel strength, and high-temperature holding power, while being solvent-free and suitable for high-temperature applications.
Smart Images

Figure 0007610632000004 
Figure 0007610632000005 
Figure 0007610632000006
Abstract
Description
[Technical field]
[0001] The present invention relates to a pressure-sensitive adhesive made from a composition consisting of a urethane prepolymer, a polythiol having a thiol group, a monomer having a photoreactive functional group, and a tackifier, and a method for producing the pressure-sensitive adhesive. [Background technology]
[0002] Conventionally, acrylic adhesives, urethane adhesives, and silicone adhesives have been used as adhesives. These adhesives often use organic solvents during production, which has been problematic in terms of their impact on the human body and the environment. In addition, the production process requires a drying step, etc., which increases production costs.
[0003] In recent years, the development of adhesives that do not require solvents has progressed, and among them, adhesives that contain a compound containing an ethylenic unsaturated bond (double bond or ene bond) and a polythiol compound with a thiol group and are produced using the ene-thiol reaction have attracted attention. In addition, in a UV curing reaction, in a typical single reaction of acrylate, peroxide radicals are generated due to the influence of oxygen in the air, but since this is inactive against the acrylate group, the radicals are deactivated and lead to the termination of polymerization, but in the ene-thiol reaction, the thiyl radical is regenerated by reacting with the peroxide radical, which has the advantage of being less susceptible to oxygen inhibition.
[0004] Patent Document 1 proposes a pressure-sensitive adhesive composition characterized in that it is formed by curing, through a photopolymerization reaction, a viscous fluid consisting of a urethane prepolymer having a terminal functional group formed on at least one of an allyl ether group and a vinyl ether group, a polythiol having a thiol group, and a tackifier.
[0005] Furthermore, Patent Document 2 proposes an adhesive composition formed by curing, by a photopolymerization reaction, a viscous fluid consisting of a urethane prepolymer having a terminal functional group formed by at least one of an allyl ether group, a vinyl ether group, and an acrylate group, a polythiol having a thiol group, and a tackifier. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2015-205989 A [Patent Document 2] JP 2016-199610 A Summary of the Invention [Problem to be solved by the invention]
[0007] Patent Document 1 discloses an invention in which a urethane prepolymer having at least one of an allyl ether group and a vinyl ether group as a terminal functional group, a polythiol having a thiol group, and a tackifier are used to form an adhesive composition by curing a viscous fluid by a photopolymerization reaction, and discloses that the adhesive exhibits moderate adhesiveness without using a solvent and without adversely affecting the human body or the environment, etc. However, use in a high-temperature environment has not been considered, and there is a risk that peel creep properties, high-temperature peel strength, high-temperature retention, initial tackiness, etc., may be insufficient in a high-temperature environment. Patent Document 2 discloses that the adhesive has high adhesion to urethane foam in addition to PP and SUS. However, the invention disclosed in Patent Document 2 uses a large amount of tackifier, so it is expected that the conformability to rough surfaces such as foam surfaces is insufficient. Furthermore, use in high temperature environments has not been considered, and since a large amount of tackifier is used, there is a risk that peel creep properties, high temperature peel strength, and high temperature retention will be insufficient in high temperature environments.
[0008] Furthermore, the large amounts of tackifiers described in the above patent documents have relatively small molecular weights and are not crosslinked, so there is a risk that sufficient adhesive strength, peel creep properties, high-temperature peel strength, and high-temperature retention may not be obtained when used at high temperatures.
[0009] Therefore, the object of the present invention is to provide an adhesive that has sufficient adhesive strength, peel creep property, high-temperature peel strength, and high-temperature retention even when used in a high-temperature environment, and can be used in a high-temperature environment. Generally, when high-temperature properties are improved, the material becomes harder (the elastic modulus, etc., becomes higher), so simply improving the high-temperature properties may result in insufficient adhesive strength or poor initial tackiness when used at room temperature. The present invention can provide an adhesive that can achieve both of these. [Means for solving the problem]
[0010] The inventors have conducted intensive research and found that the above-mentioned problems can be solved by blending a specific urethane prepolymer, a polythiol having a thiol group, a monomer having a photoreactive functional group, and a tackifier, and have completed the present invention. That is, the present invention is as follows. The present invention (1) is A pressure-sensitive adhesive made from a composition containing a urethane prepolymer, a polythiol, a resin containing a photoreactive functional group, and a tackifier, (A) The urethane prepolymer is A method for producing a polyol using polyol, a monool not containing a photoreactive functional group, a monool containing a photoreactive functional group, and a polyisocyanate as raw materials, (B) the ratio of the number of moles (a) of photoreactive functional groups present at the terminals of the urethane prepolymer to the number of moles (b) of non-photoreactive functional groups present at the terminals of the urethane prepolymer, {(a) / (b)}, is 1.5 to 9.0; (C) the average number of photoreactive functional groups in the resin containing a photoreactive functional group is 1 or more and less than 3, (D) the blending amount of the resin containing a photoreactive functional group is 2 to 15 parts by mass relative to 100 parts by mass of the urethane prepolymer, (E) The pressure-sensitive adhesive is characterized in that the softening point of the tackifier is 100° C. or higher. The present invention (2) is The pressure-sensitive adhesive of the invention (1) is characterized in that the prepolymer has a number average molecular weight of 8,000 to 20,000. The present invention (3) is The pressure-sensitive adhesive according to the invention (1) or (2), wherein the amount of the tackifier is 2 to 20 parts by mass relative to 100 parts by mass of the urethane prepolymer. The present invention (4) is The pressure-sensitive adhesive according to any one of the above inventions (1) to (3), wherein the blending amount of the polythiol is such that the SH index of the pressure-sensitive adhesive is 80 to 200. The present invention (5) is The pressure-sensitive adhesive according to any one of the above inventions (1) to (4), wherein the resin containing a photoreactive functional group is an acrylic monomer. The present invention (6) is A substrate (or core material); The adhesive tape comprises: an adhesive layer comprising the adhesive of any one of the above inventions (1) to (5) provided on at least one surface of a substrate (or core material). The present invention (7) is A step of subjecting a composition including a polyol, a monol not including a photoreactive functional group, a monol including a photoreactive functional group, and a polyisocyanate to a urethane reaction to prepare a urethane prepolymer; A mixing step of mixing the urethane prepolymer, a polythiol, a resin having a photoreactive functional group, and a tackifier; and An irradiation step of irradiating the mixture obtained by the mixing with light, and producing the adhesive by a photopolymerization reaction. Effect of the Invention
[0011] According to the present invention, it is possible to provide an adhesive and an adhesive tape that have sufficient adhesive strength, peel creep properties, high-temperature peel strength, high-temperature holding power, and initial tackiness even when used in a high-temperature environment, and that can be used in a high-temperature environment. [Brief description of the drawings]
[0012] [Figure 1] FIG. 2 is a schematic diagram showing the structure of a urethane compound contained in a urethane prepolymer. [Diagram 2] FIG. 2 is a schematic diagram showing a measurement method for evaluating peel creep properties. [Diagram 3] FIG. 2 is a schematic diagram showing a measurement method for evaluating high-temperature peel strength (90° peel test). [Figure 4] FIG. 2 is a schematic diagram showing a method for measuring heat resistance retention. [Diagram 5] FIG. 2 is a schematic diagram showing a measurement method for evaluating initial tackiness. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The pressure-sensitive adhesive, pressure-sensitive adhesive tape, and pressure-sensitive adhesive production method of the present invention will be described in detail below. In the present application, high temperature refers to a temperature of 60 to 90°C.
[0014] <<Adhesive>> The pressure-sensitive adhesive according to the present invention is made from a composition containing a urethane prepolymer, a polythiol having a thiol group, a resin having a photoreactive functional group, and a tackifier. The adhesive is characterized by being cured by crosslinking through an ene-thiol reaction between a urethane prepolymer having a photoreactive functional group and a polythiol having a thiol group. Therefore, it can be prepared without using a solvent, and since oxygen inhibition does not occur during curing, it is characterized by not requiring the installation of a cover film or the work under a nitrogen atmosphere when curing by light irradiation.
[0015] 1. Raw material composition 1-1. Urethane prepolymer The urethane prepolymer in the present invention is a urethane prepolymer containing a polyol, a monol not containing a photoreactive functional group, a monol containing a photoreactive functional group, and a polyisocyanate.
[0016] The following four types of urethane compounds are generated in the urethane prepolymer. Therefore, the prepolymer in the present invention is a mixture containing a plurality of the following four types of urethane compounds. (1) A urethane compound produced by a urethane reaction between a polyol, a monool containing a photoreactive functional group, and a polyisocyanate, i.e., a urethane compound in which all of the multiple terminals present in the urethane compound are reactive photoreactive functional groups.
[0017] (2) A urethane compound produced by a urethane reaction between a polyol, a monol not containing a photoreactive functional group, a monol containing a photoreactive functional group, and a polyisocyanate, the urethane compound having reactive photoreactive functional groups at multiple ends and no reactive photoreactive functional groups at the remaining ends (i.e., having non-reactive ends).
[0018] (3) A urethane compound produced by a urethane reaction between a polyol, a monol not containing a photoreactive functional group, a monol containing a photoreactive functional group, and a polyisocyanate, in which one end of the urethane compound has a reactive photoreactive functional group and the remaining end does not have a photoreactive functional group (i.e., has a non-reactive end).
[0019] (4) A urethane compound produced by a urethane reaction between a polyol, a monol not containing a photoreactive functional group, and a polyisocyanate, i.e., a urethane compound in which all of the multiple terminals present in the urethane compound are non-reactive. FIG. 1 shows schematic diagrams of the above four types of urethane compounds. Here, reference numeral 10 denotes a photoreactive functional group end. Reference numeral 11 denotes a non-photoreactive functional group end. The curves indicated by reference numeral 12 represent the polymer main chain and side chains.
[0020] When the urethane compounds (1) and (2) are irradiated with light, their photoreactive functional groups crosslink. When the urethane compound (3) is irradiated with light, one of the photoreactive functional groups crosslinks with the other urethane compounds (1) and (2) and the other (3), and the urethane compound (3) is formed as a side chain of the other urethane compounds. When the urethane compound (4) is irradiated with light, it does not crosslink and remains in the composition as a sol component.
[0021] The highly cross-linked urethane compounds derived from (1) and (2) above have the characteristics of improving the cohesive strength as an adhesive and enhancing the shear mechanical properties (holding strength, etc.) and high-temperature properties (adhesion strength in high-temperature environments, peel creep properties, high-temperature peel strength, high-temperature holding strength).
[0022] Here, peel creep property refers to the ability of an adhesive, tape, etc., to resist the phenomenon of peeling off after creep deformation caused by the application of a load when used in a high-temperature environment. For example, when the adhesive of the present invention is made into a tape or the like and an object to be joined is attached to the ceiling of a building, the adhesive is always under load due to the weight of the object to be joined. At this time, the adhesive creeps and peels off. In other words, peel creep property is a characteristic value that indicates the difficulty of peel creep.
[0023] Holding power is the ability of an adhesive to withstand a static load in the shear direction (shear direction), and is an index of the adhesive's creep characteristics. It is therefore used as an index of an adhesive's hardness / softness and stability against temperature. In other words, as holding power increases, the adhesive becomes harder (its modulus of rigidity increases) and its heat resistance (heat resistance temperature) also increases.
[0024] In order to increase the holding power and high temperature properties, for example, it is possible to adjust by increasing the internal energy of the adhesive. Specifically, a method of making the main skeleton rigid by increasing the molecular weight or increasing the degree of crosslinking is used. However, in general, when the holding power and high temperature properties are increased, for example, the flexibility of the adhesive decreases, so that the adhesive power, initial tackiness, and ability to follow the rough surface of the adherend decrease. The holding power and high temperature properties of the pressure-sensitive adhesive can be measured by the methods described below.
[0025] The urethane compound having the side chain structure derived from the above (3) has a small number of crosslinking points, and is characterized in that it improves the flexibility of the adhesive to conform to uneven rough surfaces such as foams.
[0026] The sol component derived from (4) above improves the adhesiveness and initial tackiness of the adhesive to poorly adhesive adherends. However, the sol component has a relatively low molecular weight, and if the content is too high, the cohesive strength of the adhesive decreases, and the shear mechanical properties (holding force, etc.) of the adhesive decrease. In addition, the high temperature properties also decrease.
[0027] The amounts of the urethane compounds (1) to (4) contained in the prepolymer are in a trade-off relationship with respect to the performance imparted to the adhesive, and the ratios can be adjusted according to the application of the adhesive. That is, if the cohesive strength derived from the compound (1) is high, the shear mechanical properties and high-temperature properties are improved, but the adhesive becomes too hard, and the adhesiveness and initial tackiness derived from the compound (3) and the rough surface conformability derived from the compound (4) are reduced. On the other hand, if there are many sol components derived from the compound (4) or many side chain structures derived from the compound (3) (few crosslinking points), the adhesiveness, initial tackiness, and rough surface conformability are improved, but the cohesive strength derived from the compound (1) is reduced, and the shear mechanical properties are reduced.
[0028] The urethane prepolymer is characterized in that the ratio of the number of moles (a) of photoreactive functional groups bonded to the end of the urethane compound contained in the urethane prepolymer to the number of moles (b) of photononreactive functional groups bonded to the end of the urethane compound is 1.5 to 9.0. This ratio determines the viscoelastic properties {degree of crosslinking, concentration (or density) of side chain structures, and amount of sol components} of the adhesive when it is crosslinked by light irradiation. Therefore, it affects the shear mechanical properties, rough surface conformability, adhesion, and high temperature properties of the adhesive. When this ratio is less than 0.4, a polymer with many side chain structures is formed, and the sol components also increase. Therefore, although the adhesion, initial tackiness, and rough surface conformability are improved, the shear mechanical properties and high temperature properties are reduced. On the other hand, when this ratio exceeds 2.5, the shear mechanical properties and high temperature properties are improved, but the adhesion, initial tackiness, and rough surface conformability are reduced.
[0029] The number of equivalents of the photoreactive functional group (a) and the number of equivalents of the non-photoreactive functional group (b) can be the number of equivalents of the monool blended before synthesis.
[0030] The number average molecular weight of the urethane prepolymer is not particularly limited, but for example, the upper limit can be 30,000, and preferably 28,000, 25,000, 23,000, 20,000, 18,000, or 15,000, and for example, the lower limit can be 5,000, and preferably 7,000, 8,000, 9,000, 10,000, or 12,000. When the number average molecular weight of the urethane prepolymer is within this range, the cohesive strength (shear mechanical properties), high temperature properties, adhesion, initial tackiness, and rough surface conformability as an adhesive can be easily adjusted to suitable ranges.
[0031] Here, the number average molecular weight can be measured by a known method. For example, it can be measured by using gel permeation chromatography, using tetrahydrofuran (THF) as an eluent, and detecting the differential refractive index. The number average molecular weight is calculated by creating a calibration curve based on the GPC measurement results of polystyrene, which is a standard sample, and calculating the measurement results of the measurement sample as a polystyrene equivalent value.
[0032] 1-1-1.Polyol The polyol contained in the urethane prepolymer is a compound having two or more hydroxyl groups in one molecule, and is not particularly limited as long as it does not impair the effects of the present invention. Examples of the polyol used in the present invention include polyester polyol, polycarbonate polyol, polyether polyol, polyester ether polyol, etc. The polyols may be used alone or in combination of two or more kinds. Since the polyol forms the skeleton of the urethane prepolymer, it can be selected taking into consideration the effect of its structure (the number of carbon atoms in the skeleton, the structure of the side chains, etc.) on cohesive strength (shear mechanical properties, high-temperature properties), adhesion, initial tackiness, and ability to conform to rough surfaces.
[0033] Examples of polyester polyols include aliphatic dicarboxylic acids such as succinic acid, adipic acid, sebacic acid, and azelaic acid, aromatic dicarboxylic acids such as phthalic acid, terephthalic acid, isophthalic acid, and naphthalenedicarboxylic acid, alicyclic dicarboxylic acids such as hexahydrophthalic acid, hexahydroterephthalic acid, and hexahydroisophthalic acid, and acid esters or acid anhydrides thereof, and ethylene glycol, 1,3-propylene glycol, 1,2-propylene glycol, and the like. , 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, neopentyl glycol, 1,8-octanediol, 1,9-nonanediol, or the like, or a mixture thereof; polyester polyols such as polypropylene glycol obtained by a dehydration condensation reaction with such a lactone monomer; and polylactone diols obtained by ring-opening polymerization of lactone monomers such as ε-caprolactone and methylvalerolactone.
[0034] Examples of polycarbonate polyols include those obtained by reacting at least one polyhydric alcohol such as ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, neopentyl glycol, 1,8-octanediol, 1,9-nonanediol, or diethylene glycol with diethylene carbonate, dimethyl carbonate, diethyl carbonate, or the like.
[0035] Examples of polyether polyols include polyethylene glycol, polypropylene glycol, polytetramethylene ether glycol, etc., which are obtained by polymerizing cyclic ethers such as ethylene oxide, propylene oxide, tetrahydrofuran, etc., and copolyethers thereof. Polyether polyols can also be obtained by polymerizing the above-mentioned cyclic ethers using polyhydric alcohols such as glycerin and trimethylolethane.
[0036] Examples of polyester ether polyols include those obtained by a dehydration condensation reaction of aliphatic dicarboxylic acids such as succinic acid, adipic acid, sebacic acid, and azelaic acid; aromatic dicarboxylic acids such as phthalic acid, terephthalic acid, isophthalic acid, and naphthalenedicarboxylic acid; alicyclic dicarboxylic acids such as hexahydrophthalic acid, hexahydroterephthalic acid, and hexahydroisophthalic acid; or acid esters or acid anhydrides of these acids with glycols such as diethylene glycol or propylene oxide adducts, or mixtures thereof.
[0037] 1-1-2. Monools that do not contain photoreactive functional groups The monool is a compound having one hydroxyl group per molecule, and not containing a photoreactive functional group means that the monool is formed only of a non-photoreactive functional group. The monool is not particularly limited as long as it can be bonded to a polyisocyanate group. For example, linear, branched or cyclic monohydric alcohols (methanol, ethanol, propanol, butanol, isobutyl alcohol, tert-butyl alcohol, pentanol, isopentyl alcohol, neopentyl alcohol, hexanol, 2-methyl-1-pentanol, octanol, 2-ethyl-1-hexanol, 3,5,5-trimethyl-1-hexanol, decanol, undecanol, 1-dodecanol, isooctadecanol, octadecenol, docosanol, 14-methylhexadecanol, cyclohexanol, methylcyclohexanol, 2-ethylhexyl glycol, etc.) can be mentioned. Further, glycol ethers such as ethylene glycol monomethyl ether, diethylene glycol monomethyl ether, ethylene glycol monoisopropyl ether, ethylene glycol monobutyl ether, and ethylene glycol monohexyl ether can be used.
[0038] Here, the photoreactive functional group is a functional group that can be crosslinked by irradiation with X-rays, electron beams, ultraviolet rays, visible light, etc., that is, a functional group having a multiple bond, and examples thereof include an alkenyl group, an alkynyl group, a vinyl group, an acrylic group, a methacrylate group, an allyl group, etc. The monol does not contain these photoreactive functional groups.
[0039] Since the monol does not contain a photoreactive functional group, it does not participate in the crosslinking reaction when irradiated with light, and exists as a sol component in the pressure-sensitive adhesive of the present invention or as a side chain of the urethane polymer. Therefore, the carbon number, linearity, and side chain structure of the monol can be selected in consideration of the effects on the cohesive strength (shear mechanical properties, high-temperature properties), adhesion, initial tackiness, and rough surface conformability of the pressure-sensitive adhesive of the present invention.
[0040] 1-1-3. Monool containing photoreactive functional group A monol is a compound having one hydroxyl group per molecule, and containing a photoreactive functional group means that the monol contains at least one photoreactive functional group. The monol is not particularly limited as long as it can be bonded to a polyisocyanate group. For example, monols having an allyl ether group such as allyl ether glycol and hydroxyethyl allyl ether; monols having a vinyl ether group such as 2-hydroxyethyl vinyl ether, diethylene glycol monovinyl ether, and 4-hydroxybutyl vinyl ether; monols having a (meth)acrylic group such as hydroxyethyl acrylate, hydroxypropyl acrylate, 4-hydroxybutyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxyethyl acrylate, and 2-hydroxypropyl methacrylate.
[0041] Here, the photoreactive functional group is a functional group that can be crosslinked by irradiation with X-rays, electron beams, ultraviolet rays, visible light, etc., that is, a functional group having a multiple bond, and examples thereof include an alkenyl group, an alkynyl group, a vinyl group, an acrylic group, a methacrylate group, an allyl group, etc. When the monol contains a plurality of photoreactive functional groups, the photoreactive functional groups can be used in combination.
[0042] The monol contains a photoreactive functional group, and therefore participates in a crosslinking reaction when irradiated with light, and exists as the main backbone or side chain of the urethane polymer in the pressure-sensitive adhesive of the present invention. Therefore, the carbon number, linear chain, and side chain structure of the monol can be selected in consideration of the effects on the cohesive strength (shear mechanical properties, high-temperature properties), adhesion, initial tackiness, and rough surface conformability of the pressure-sensitive adhesive of the present invention.
[0043] 1-1-4. Polyisocyanate The polyisocyanate is a compound having two or more isocyanate groups in one molecule, and is not particularly limited as long as it is a compound that is usually used as a raw material for urethane prepolymers. For example, bifunctional polyisocyanates include 2,4-toluene diisocyanate (2,4-TDI), 2,6-toluene diisocyanate (2,6-TDI), m-phenylene diisocyanate, p-phenylene diisocyanate, 4,4'-diphenylmethane diisocyanate (4,4'-MDI), 2,4'-diphenylmethane diisocyanate (2,4'-MDI), 2,2'-diphenylmethane diisocyanate (2,2'-MDI), hydrogenated MDI, xylylene diisocyanate, 3,3'-dimethyl diisocyanate, ... Aromatic isocyanates such as ethyl-4,4'-biphenylene diisocyanate, 3,3'-dimethoxy-4,4'-biphenylene diisocyanate, polymethylene polyphenyl polyisocyanate, 1,5-naphthalene diisocyanate, xylylene diisocyanate (XDI), hydrogenated XDI, tetramethyl xylene diisocyanate (TMXDI), cyclohexane-1,4-diisocyanate, isophorone diisocyanate, dicyclohexylmethane-4,4'-diisocyanate, methylcyclohexane diisocyanate, Alicyclic isocyanates such as isocyanate, alkylene-based isocyanates such as butane-1,4-diisocyanate, hexamethylene diisocyanate, isopropylene diisocyanate, methylene diisocyanate, and lysine diisocyanate, and trifunctional or higher polyisocyanates such as 1-methylbenzene-2,4,6-triisocyanate, 1,3,5-trimethylbenzene-2,4,6-triisocyanate, biphenyl-2,4,4'-triisocyanate, and diphenylmethane-2,4,4'-triisocyanate. tetraisocyanate, methyldiphenylmethane-4,6,4'-triisocyanate, 4,4'-dimethyldiphenylmethane-2,2',5,5'tetraisocyanate, triphenylmethane-4,4',4"-triisocyanate, polymeric MDI, lysine ester triisocyanate, 1,3,6-hexamethylene triisocyanate, 1,6,11-undecane triisocyanate, bicycloheptane triisocyanate, 1,8-diisocyanatomethyloctane, and the like, as well as modified products and derivatives thereof. The polyisocyanate exists as a part of the sol component in the pressure-sensitive adhesive of the present invention or the skeleton of the urethane polymer. Therefore, the carbon number, linear or side chain structure of the polyisocyanate can be selected in consideration of the effects on the cohesive strength (shear mechanical properties, high-temperature properties), adhesion, initial tackiness, and rough surface conformability of the pressure-sensitive adhesive of the present invention.
[0044] 1-1-5. Catalyst In the synthesis of the urethane prepolymer, a reaction catalyst may be added to promote the reaction or increase the reaction rate. The reaction catalyst is not particularly limited, and includes known catalysts such as metal catalysts, for example, tin catalysts, lead catalysts, other metal catalysts, amine catalysts, other acid catalysts, and basic catalysts. One or more of these catalysts can be used.
[0045] 1-2. Resin with photoreactive functional groups The resin having a photoreactive functional group is a compound having an average of 1 to less than 3 photoreactive functional groups in one molecule contained in the resin, more preferably 1 to 2 on average. The photoreactive functional groups may all be the same functional group, or may contain different functional groups. These photoreactive functional groups crosslink with the urethane prepolymer and / or polythiol by a crosslinking reaction caused by light irradiation.
[0046] In the urethane prepolymer of the present invention, if a side chain structure is introduced by increasing the ratio of non-reactive terminals of the urethane prepolymer, the sol content increases too much, and the peel creep property at high temperatures decreases. By adding the resin, the adhesive's cohesive strength (shear mechanical properties, high temperature properties), adhesion, initial tackiness, and rough surface conformability can be balanced by introducing an appropriate branch and side chain structure. Here, in this specification, the resin includes a monomer, an oligomer, and a polymer.
[0047] The number average molecular weight of the resin is not particularly limited, but is preferably smaller than the number average molecular weight of the urethane prepolymer. When the molecular weight is smaller, the reactivity to light irradiation is high, and the resin can be efficiently incorporated into the molecular structure to form a branched or side chain structure. From this viewpoint, a monomer is preferable, and an acrylic monomer is more preferable.
[0048] Here, the photoreactive functional group is a functional group that can be crosslinked by irradiation with X-rays, electron beams, ultraviolet rays, visible light, or the like, i.e., a functional group having a multiple bond, and examples of such functional groups include an alkenyl group, an alkynyl group, a vinyl group, an acrylic group, a methacrylate group, and an allyl group.
[0049] The resin is not particularly limited as long as it has a photoreactive functional group. For example, acrylic resin, urethane resin, ethylene-vinyl acetate resin, vinyl chloride resin, vinyl acetate resin, styrene resin, vinyl alcohol resin, vinylpyrrolidone resin, vinyl butyral resin, methacrylate resin, and allyl ether group can be mentioned. In addition, a plurality of the above resins can be mixed and used.
[0050] The blending amount of the resin is 2 to 15 parts by mass when the blending amount of the polyurethane prepolymer is taken as 100 parts by mass. By setting the blending amount of the resin in this range, it is possible to obtain a pressure-sensitive adhesive that has sufficient adhesive strength to adherends that are difficult to adhere to and have large unevenness, such as rubber foams and PE foams, and that has sufficient adhesive strength, peel creep properties, high-temperature peel strength, high-temperature holding power, and initial tackiness even when used in a high-temperature environment and can be used in a high-temperature environment.
[0051] 1-3. Polythiol The polythiol is a compound having two or more thiol groups in one molecule, and is not particularly limited as long as it does not impair the effects of the present invention. Examples of polythiols that undergo an ene-thiol reaction with the urethane prepolymer obtained from the above compound include esters of mercaptocarboxylic acids and polyhydric alcohols, aliphatic polythiols, and aromatic polythiols. Examples of aliphatic polythiols and aromatic polythiols include ethanedithiol, propanedithiol, hexamethylenedithiol, decamethylenedithiol, tolylene-2,4-dithiol, and xylenedithiol.
[0052] In addition, in the esters of mercaptocarboxylic acids and polyhydric alcohols, examples of the mercaptocarboxylic acids include thioglycolic acid and mercaptopropionic acid, and examples of the polyhydric alcohols include ethylene glycol, propylene glycol, 1,4-butanediol, 1,6-hexanediol, glycerin, trimethylolpropane, pentaerythritol, and sorbitol. Among these, esters of mercaptocarboxylic acids and polyhydric alcohols are preferred because they have little odor, and specific examples include trimethylolpropane tris(3-mercaptopropionate), pentaerythritol tetrakis(3-mercaptopropionate), tetraethylene glycol bis(3-mercaptopropionate), and dipentaerythritol hexa(3-mercaptopropionate). It is possible to use one or more of these various polythiols in combination as a raw material for the ene-thiol reaction with the urethane prepolymer.
[0053] By mixing the polythiol with the urethane prepolymer and subjecting them to a polymerization reaction (ene-thiol reaction), an ene-thiol adhesive composition having high flexibility can be obtained. Here, the polymerization reaction may be a photopolymerization reaction or a thermal polymerization reaction. In the case of the photopolymerization reaction, the ene-thiol reaction is advanced by mixing the above-mentioned polythiol with the urethane prepolymer and then irradiating it with light (ultraviolet rays, etc.). The reaction mechanism in the case of the thermal polymerization reaction is the same as that in the case of the photopolymerization reaction, and the only difference is whether the generation of radicals is due to light or heat. Here, since the polymerization reaction proceeds faster in the photopolymerization reaction than in the thermal polymerization reaction, it is preferable to utilize the photopolymerization reaction in the method for producing the adhesive composition according to the present invention.
[0054] In addition, by combining the above-mentioned polythiols with a functional group (thiol group) of two (bifunctional thiol) with a functional group of more than two (trifunctional or higher thiol), it is possible to obtain an ene-thiol adhesive composition with even higher flexibility. Specifically, by setting the average number of functional groups of the thiol groups reacting with the urethane prepolymer, that is, the average number of functional groups of the thiol groups of a polythiol with two thiol groups and a polythiol with three or more thiol groups, to 2.5 or more, an ene-thiol adhesive composition with high flexibility can be obtained.
[0055] 1-4. Tackifier The tackifier has a softening point of 100° C. or higher. The tackifier is not particularly limited as long as it has a softening point of 100° C. or higher. Examples of the tackifier include rosin resins, terpene resins, aliphatic petroleum resins, alicyclic petroleum resins, aromatic petroleum resins, chromalon-indene resins, styrene resins, phenolic resins, and xylene resins. These can be used alone or in combination. The amount of the tackifier can be 2 to 20 parts by mass relative to 100 parts by mass of the urethane prepolymer. When the amount of the tackifier is within this range, the adhesive has sufficient adhesion to adherends that are difficult to adhere to and have large unevenness, such as rubber foams and PE foams, and has sufficient adhesion, peel creep, high-temperature peel strength, high-temperature retention, and initial tackiness even when used in a high-temperature environment, and can be used in a high-temperature environment.
[0056] 1-5.Other additives As another additive, the adhesive composition of the present invention may contain a photopolymerization initiator in order to effectively carry out the polymerization reaction between the urethane prepolymer and resin and the thiol group. Examples of the photopolymerization initiator used in the photopolymerization reaction include acetophenone-based, benzophenone-based, and thioxanthone-based compounds. Examples of acetophenones include 2,2-dimethoxy-2-phenylacetophenone, 1,1-dichloroacetophenone, 4-(1-t-butyldioxy-1-methylethyl)acetophenone, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholino-propan-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1, diethoxyacetophenone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, benzyl dimethyl ketal, 4-(2-hydroxyethoxy)phenyl-(2-hydroxy-2-propyl)ketone, 1-hydroxycyclohexyl phenyl ketone, and 2-hydroxy-2-methyl-1-[4-(1-methylvinyl)phenyl]propanone oligomer.
[0057] Examples of benzophenones include 4-(1-t-butyldioxy-1-methylethyl)benzophenone, 3,3',4,4'-tetrakis(t-butyldioxycarbonyl)benzophenone, o-benzoylmethylbenzoate, 4-phenylbenzophenone, 4-benzoyl-4'-methyl-diphenyl sulfide, 3,3',4,4'-tetra(t-butylperoxycarbonyl)benzophenone, 2,4,6-trimethylbenzophenone, 4-benzoyl-N,N-dimethyl-N-[2-(1-oxo-2-propenyloxy)ethyl]benzenemethanaminium bromide, and (4-benzoylbenzyl)trimethylammonium chloride. Examples of thioxanthone include 2,4-dimethylthioxanthone, 2,4-diisopropylthioxanthone, 2-chlorothioxanthone, 2-isopropylthioxanthone, 4-isopropylthioxanthone, 2,4-diethylthioxanthone, 2,4-dichlorothioxanthone, 1-chloro-4-propoxythioxanthone, and 2-(3-dimethylamino-2-hydroxy)-3,4-dimethyl-9H-thioxanthone-9-one mesochloride.
[0058] Furthermore, the raw material composition of the present invention may contain various additives, if necessary, in addition to the above-mentioned components, within the range that does not impair the effects of the present invention. Examples of additives include fillers, plasticizers, pigments, dyes, antioxidants, antioxidants, antistatic agents, flame retardants, antibacterial agents, light stabilizers, stabilizers, dispersants, etc.
[0059] 2. Method for producing raw material composition The formulation of the raw material composition according to the present invention is described in detail below. 2-1. Amount of raw material composition The amount of the polyol blended in the synthesis of the urethane prepolymer is 100 parts by mass. The monol is blended so that the ratio of the number of equivalents (a) of photoreactive functional groups bonded to the terminals of the urethane compounds contained in the urethane prepolymer mixture described above to the number of equivalents (b) of photonon-reactive functional groups bonded to the terminals of the urethane compounds is 1.5 to 9.0.
[0060] The polyisocyanate can be blended such that all of the hydroxyl groups react with the isocyanate groups by calculating the hydroxyl group equivalent from the blend amounts of the polyol and monol.
[0061] <Mixing step of mixing urethane prepolymer, polythiol, resin having photoreactive functional group, and tackifier> The blending amount of the resin is adjusted to 2 to 15 parts by mass when the blending amount of the urethane prepolymer is taken as 100 parts by mass.
[0062] The polythiol is not particularly limited, but may be blended so that the thiol-ene (thiol group / double bond) ratio is 0.7 to 2.5, preferably 0.8 to 2.0, relative to the double bond equivalent number of the photoreactive functional group. When this ratio is within this range, oxygen inhibition is unlikely to occur, the surface curing property is good, and excellent adhesive properties (especially adhesive properties under high temperature environment) are exhibited, and since there are no excess thiol groups, the thiol groups do not inhibit the reaction with each other, a sufficient degree of crosslinking can be achieved, and excellent high temperature properties are exhibited. The thiol-ene (double bond) ratio can also be expressed as a thiol index (SH index). The thiol index is a ratio of the number of moles of thiol groups to the number of moles of double bond groups in a thiol compound multiplied by 100, and can be 70 to 250, and preferably 80 to 200.
[0063] 2-2. Method for producing urethane prepolymer (process for producing urethane prepolymer) The method for producing the urethane prepolymer is not particularly limited, and any known method can be used, one example of which is described below. A mixture of polyisocyanate is placed in a container and stirred under a nitrogen atmosphere. A polyol is added dropwise to the container. A catalyst can be added as necessary to promote the reaction. The amount of catalyst added is not particularly limited, but can be, for example, 0.01 to 5 parts by mass. The mixture is stirred for a predetermined time to complete the reaction. At this point, a portion of the reaction product is sampled and the isocyanate group content is measured to confirm that it is within the desired range. After confirmation, a monol containing a photoreactive functional group and a monol not containing a photoreactive functional group are added, and the mixture is reacted for a predetermined time to form a prepolymer.
[0064] 2-3. Method for producing raw material composition (mixing step of mixing urethane prepolymer, polythiol, resin having photoreactive functional group, and tackifier) The method for producing the raw material composition is not particularly limited, and any known method can be used, one example of which is described below. While stirring the obtained urethane prepolymer, a resin having a photoreactive group, a polythiol, and a tackifier are added in predetermined amounts to prepare a raw material composition.
[0065] 2-4. Method for forming adhesive tape (including an irradiation step of irradiating the mixture obtained in the mixing step with light) The method for forming the adhesive tape is not particularly limited, and any known method can be used, one example of which is described below. The obtained raw material composition is applied to a release paper to a predetermined thickness, and then the applied raw material composition is cured by light irradiation to become an adhesive (adhesive layer). The adhesive (adhesive layer) formed on the release paper can be used to form a single-sided tape by further laminating a substrate to the adhesive surface. In addition, the adhesive formed on the release paper can be attached to both sides of a core material to form a double-sided tape.
[0066] The release paper is composed of a paper substrate and a release layer formed on the surface thereof, and is easily peeled off from the adhesive. The substrate of the release paper is not limited to paper, and a known resin film can be used. For example, a PET film or an OPP film can be used. The thickness of the substrate is not particularly limited, and can be, for example, 10 to 200 μm. The release layer can be formed using a known release agent, for example, a silicone compound such as dimethylsiloxane.
[0067] The coating method is not particularly limited and may be performed by a known method, for example, a comma coater, a die coater, a gravure coater, etc. A die coater is preferable because it is possible to adjust the temperature during coating and the coating viscosity of the raw material composition.
[0068] The thickness of the raw material composition coated on the release paper is not particularly limited, and can be, for example, 10 to 500 μm.
[0069] The light irradiation is performed by irradiating light of a specific wavelength at which the photoreactive functional group reacts or at which the added photopolymerization initiator acts. The amount of light irradiation can be set depending on the blending and thickness of the raw material composition, the type and amount of the photopolymerization initiator, etc., and is, for example, 600 to 1800 mJ / cm. 2 When Omnirad 1173 (manufactured by IGM Resins) is used as the photopolymerization initiator, the composition can be cured by irradiating it with light having a wavelength of 365 nm.
[0070] The substrate used when forming the single-sided tape is not particularly limited, and known films, papers, etc. can be used. For example, PET film, OPP film, etc. can be used. The thickness of the substrate is not particularly limited, and can be, for example, 10 to 200 μm.
[0071] The core material used in forming the double-sided tape is not particularly limited, and known core materials can be used. For example, all-pulp (14 g / m 2 The thickness of the core material is not particularly limited, and can be set to 10 to 500 μm.
[0072] 3. Applications of adhesive tape The pressure sensitive adhesive can be used as a double-sided tape mainly used in high temperature environments. Specifically, it is suitable for applications requiring peel creep properties, such as fixing a foam to a curved surface used at high temperatures. In addition, since it has excellent rough surface conformability, it can be used to fix materials such as polyethylene foam and some rubber foam that are difficult to adhere to and difficult to fix with conventional pressure sensitive adhesives. Foams such as polyethylene foam are widely used in industry as sealing materials, sound absorbing materials, and shock absorbing materials, but their applications have been limited due to their poor adhesion. EXAMPLES
[0073] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to these examples and can be practiced in various forms with various modifications and improvements based on the knowledge of those skilled in the art. (raw materials) The following raw materials were weighed out according to Tables 1 to 3 and mixed together. Polyol A: Polypropylene glycol, molecular weight 3000 Polyol B: Polypropylene glycol, molecular weight 200 Monool that does not contain a photoreactive functional group: Lauryl alcohol Monool containing photoreactive functional group: Hydroxyethyl acrylate Polyisocyanate: Tolylene diisocyanate (2,4-tolylene diisocyanate: 80%, 2,6-tolylene diisocyanate: 20%) Resin A: Phenoxyethyl acrylate (photoreactive functional group number 1) Number average molecular weight 192.2 Resin B: 1,9-nonanediol diacrylate (photoreactive functional group number 2) Number average molecular weight 268.4 Resin C: Trimethylolpropane triacrylate (photoreactive functional group number 3) Tackifier A: Super Ester A115, softening point 115°C (Arakawa Chemical Industries, Ltd.) Tackifier B: Super Ester A100, softening point 100°C (Arakawa Chemical Industries, Ltd.) Tackifier C: Super Ester A125, softening point 125°C (Arakawa Chemical Industries, Ltd.) Tackifier D: Super Ester A75, softening point 75°C (Arakawa Chemical Industries, Ltd.) Polythiol: Trimethylolpropane tris(3-mercaptopropionate) (molecular weight: 398.5, average number of functional groups: 3) Initiator: Omnirad 1173 (IGM Resins)
[0074] (Preparation of urethane prepolymer) The amounts of the raw materials were weighed according to Table 1. The polyisocyanate was placed in a separate flask in the amount required and stirred under a nitrogen atmosphere. Polyols A and B were then added dropwise. After the addition was complete, 0.3 g of catalyst (dibutyltin dilaurate) was added. After reacting for 3 hours, a portion was sampled and the isocyanate group content was measured, and it was confirmed that it was within the range for each prepolymer below. The isocyanate content was measured in accordance with the method based on JIS Z1603-1:2007 (Testing method for aromatic isocyanates used as polyurethane raw materials). Next, each monol was dropped and reacted for 2 hours. After the reaction, a sample was taken to confirm that the isocyanate group content was 0.05% or less. When the isocyanate group content was 0.05% or less, the reaction was considered complete and the product was named urethane prepolymer A. Prepolymers B to H were prepared in the same manner according to Table 1. Prepolymer A: Isocyanate content 0.7-1.1% Prepolymer B: Isocyanate content 0.7~1.1% Prepolymer C: Isocyanate content 0.7~1.1% Prepolymer D: Isocyanate content 0.7-1.1% Prepolymer E: Isocyanate content 0.7-1.1% Prepolymer F: Isocyanate content 0.9~1.3% Prepolymer G: Isocyanate content 0.4~0.8% Prepolymer H: Isocyanate content 0.2-0.6%
[0075] [Table 1]
[0076] (Method of producing raw material composition) The raw material composition of Example 1 was prepared by adding prescribed amounts of resin B, resin C, polythiol, and tackifier to prepolymer A weighed according to Table 2 while stirring the prepolymer A. In Examples 2 to 15 and Comparative Examples 1 to 6, the raw material compositions of Examples 2 to 15 and Comparative Examples 1 to 6 were obtained in the same manner as in Example 1, except that the blending amounts were changed to those shown in Table 2.
[0077] (Method of forming adhesive tape) The raw material composition of Example 1 was coated on release paper to a predetermined thickness and irradiated with light (wavelength: 365 nm, irradiation dose: 800 mJ / cm 2 ) to harden it into an adhesive. A PET film (thickness: 25 μm) was further laminated to the adhesive surface of the adhesive formed on the release paper to obtain the single-sided adhesive tape of Example 1. In Examples 2 to 15 and Comparative Examples 1 to 6, the adhesive tapes of Examples 2 to 15 and Comparative Examples 1 to 6 were obtained in the same manner as in Example 1, except that the blending amounts were changed to those shown in Table 2.
[0078] (evaluation) -Evaluation of peel creep properties The adhesive tapes prepared using the adhesives of Examples 1 to 15 and Comparative Examples 1 to 6 were processed into a shape of 25 mm wide x 180 mm long to prepare test samples. A polypropylene plate processed into a shape of 30 mm wide x 150 mm long x 5 mm thick was used as the adherend. The test sample and the adherend were laminated together using a rubber roller weighing 5 kg, moving back and forth at a speed of 5 mm / sec. so that the length of the laminated part was 100 mm. The sample was then left to stand for 4 hours and used for measurement. The sample was then placed in an oven at 80°C and a 20 g weight was hung from it (see FIG. 2). The sample was then left to stand for 24 hours, and the length by which the sample peeled off from the polypropylene plate was taken as the measured value of peel creep. The results were evaluated according to the following evaluation criteria. The evaluation results are shown in Tables 2 and 3. ○: Peeling length is less than 25 mm △: When the peeled length is 25mm or more but less than 50mm ×: When the peeled length is 50 mm or more
[0079] High temperature peel strength evaluation (90° peel test) The adhesive tapes prepared using the adhesives of Examples 1 to 15 and Comparative Examples 1 to 6 were processed into a shape of 25 mm wide x 200 mm long to prepare test samples. In addition, a SUS304 plate processed into a shape of 30 mm wide x 350 mm long x 5 mm thick was used as an adherend. The test sample and the adherend were rolled back and forth once at a speed of 5 mm / sec. using a rubber roller weighing 2 kg to bond the entire surface of the sample. Next, the sample was left to stand at room temperature for 30 minutes, and then left to stand in an environment (oven) at 80°C for 10 minutes to be used for measurement. The peel strength was measured by carrying out a 90° peel test using a material testing machine equipped with a thermostatic bath (Shimadzu Corporation: Autograph AG-X) (see FIG. 3). The measurement was carried out by fixing a portion of the test sample and the adherend 10 mm from the end to the chuck of the material testing machine and peeling at a tensile speed (crosshead speed) of 300 mm / min. The measurement result was the tensile strength at the time of the peeling, which was taken as the peel strength. The results were evaluated according to the following evaluation criteria. The evaluation results are shown in Tables 2 and 3. ○: Peel strength is 7N or more △: Peel strength is between 4N and 7N ×: Peel strength is less than 4
[0080] ·Heat-resistant holding force measurement The adhesives prepared using the adhesives of Examples 1 to 16 and Comparative Examples 1 to 6 were processed into a shape of 25 mm wide x 200 mm long to prepare test samples. In addition, a stainless steel plate (SUS304: JIS G4305:2012 "Cold-rolled stainless steel plate and strip") processed into a shape of 30 mm wide x 350 mm long x 5 mm thick was used as an adherend. The test sample and the adherend were bonded together at a speed of 5 mm / sec. using a rubber roller weighing 2 kg so that the bonding area between them was 25 mm x 25 mm. The sample was then left to stand for 15 minutes (measurement sample) and used for measurement. The heat resistance holding power was measured by fixing the adherend of the measurement sample in an oven adjusted to 80°C, and then hanging a 500g weight on the adhesive tape side (see Figure 4). The amount of displacement one hour after hanging the weight was measured, and this was taken as the heat resistance holding power. The results were evaluated according to the following evaluation criteria. The evaluation results are shown in Tables 2 and 3. ○: When the tape misalignment is less than 5 mm △: The tape misalignment is between 5mm and 10mm ×: If the tape is misaligned by 10 mm or more
[0081] Initial tack evaluation The pressure-sensitive adhesives of Examples 1 to 16 and Comparative Examples 1 to 6 were formed on release paper to a thickness of 200 μm, and then the end surface area was 2 cm 2 The adhesive was attached to the end surface of a cylindrical iron bar. A 5 cm square cubic urethane foam was fixed to a test stand, and the end surface of the iron bar with the adhesive attached was pressed vertically against the top surface of the urethane foam, a force of 0.2 N was applied, and the surface was left stationary for 3 seconds. The iron bar was then pulled up vertically at a speed of 300 mm / min, and the strength at which the adhesive peeled off from the urethane foam was measured, which was taken as the measured value for the initial tackiness (see Figure 5). The results were evaluated according to the following evaluation criteria. The evaluation results are shown in Tables 2 and 3. ○: Strength is 1.0N or more △: When the strength is 0.5 or more and less than 1.0 N ×: Peel strength is less than 0.5
[0082] ·comprehensive evaluation The results of the peel creep property evaluation, high temperature peel strength evaluation, heat resistance retention evaluation and initial tackiness evaluation were comprehensively evaluated based on the following criteria. The results are shown in Tables 2 and 3. ○: The evaluation results show two or more ○ and no × △: In the above evaluation results, there is one ○ and the rest are all △ ×: If there is even one × in the evaluation results
[0083] [Table 2]
[0084] [Table 3]
[0085] (Evaluation Results) The results in Tables 2 and 3 show the effects of the present invention. [Explanation of symbols]
[0086] 1. Urethane compounds 10 Photoreactive functional groups 11. Non-photoreactive functional groups 12 Polymer main chain and side chain 2. Peel creep property evaluation device 20 Adhesive tape (test sample) 21 Polypropylene plate 22 Weight 3 High temperature peel strength evaluation (90° peel test) device 30 Adhesive tape (test sample) 31 Polypropylene plate 32 Lifting equipment 4 Heat-resistant holding force measuring device 40 Adhesive tape (test sample) 41 Stainless steel plate 42 Lifting equipment 43 Weight 5. Initial tack evaluation device 50 Adhesive tape (test sample) 51 Horizontal Bar 52 Urethane foam
Claims
1. A pressure-sensitive adhesive made from a composition containing a urethane prepolymer, a polythiol, a compound containing a photoreactive functional group, and a tackifier, (A) The urethane prepolymer is A method for producing a polyol using polyol, a monool not including a photoreactive functional group, a monool including a photoreactive functional group, and a polyisocyanate as raw materials, (B) the ratio of the number of moles (a) of photoreactive functional groups present at the terminals of the urethane prepolymer to the number of moles (b) of non-photoreactive functional groups present at the terminals of the urethane prepolymer, {(a) / (b)}, is 1.5 to 9.0; (C) the average number of photoreactive functional groups in the compound containing a photoreactive functional group is 1 or more and less than 3, (D) the blending amount of the compound containing a photoreactive functional group is 2 to 15 parts by mass relative to 100 parts by mass of the urethane prepolymer, (E) The tackifier has a softening point of 100° C. or higher, and is blended in an amount of 2 to 20 parts by mass relative to 100 parts by mass of the urethane prepolymer. A pressure-sensitive adhesive comprising:
2. A substrate (or core material); An adhesive tape comprising: an adhesive layer comprising the adhesive according to claim 1 provided on at least one surface of a substrate (or core material).
Citation Information
Patent Citations
Adhesive composition and method for producing adhesive composition
JP2015205989A
Tackifier, adhesive composition, and method for producing adhesive composition
JP2016199610A
Adhesive composition and adhesive sheet using the same
JP2017052948A
Adhesive, and production method of adhesive
JP2018111765A
Adhesive, adhesive tape, and method for producing adhesive
JP2021004301A